Economic feasibility of private nonprofit salmon hatcheries : an introduction - Orth, Franklin L.; Alaska Sea Grant Program. (Fairbanks : University of Alaska Sea Grant Program, 1975)
At head of title: Aquaculture notes. Includes bibliographical references. Mode of access: Internet. 17